From Novice to Expert: Masters’ ELT Students’ Voices on the Emotional Geography in Thesis Proposal Writing Difficulties - Shofiatu Fikri; Sumardi Sumardi; Kristian Adi Putra (AL-ISHLAH: Jurnal Pendidikan, 2024)
Research on the emotions felt by master’s students in the face of difficulties during the process of writing a thesis proposal has been scarce in higher education.  This study adopted a qualitative approach, while the type of research was a narrative inquiry. This study used semi-structured interviews to explore three masters' ELT students’ emotional geography in      writing thesis proposals at a university in Indonesia and using thematic analysis to analyze the data. This study was framed by Emotional Geography (EG) as a means for understanding masters' ELT students' voices in thesis proposal writing. This result revealed that masters’ ELT students experienced various emotions, such as positive and negative emotions, that arise through their relationship and interaction with their thesis supervisor, which influenced the writing of their thesis proposal. As such, EG has provided insight about the role of emotional aspects which thesis supervisors can apply as a strategy for building relationships with students that support the proposal writing process.